2016
DOI: 10.1088/0957-4484/27/40/402002
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled peptide nanostructures for functional materials

Abstract: Nature is an important inspirational source for scientists, and presents complex and elegant examples of adaptive and intelligent systems created by self-assembly. Significant effort has been devoted to understanding these sophisticated systems. The self-assembly process enables us to create supramolecular nanostructures with high order and complexity, and peptide-based self-assembling building blocks can serve as suitable platforms to construct nanostructures showing diverse features and applications. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 440 publications
(512 reference statements)
2
70
0
2
Order By: Relevance
“…While concerns about amyloidogenic potential of these beta structured peptides need further attention, in vitro and in vivo studies thus far have shown several classes of peptide‐based materials to be biocompatible . Beta‐sheet forming peptides often have the sequence (ZXZX) n , where Z and X represent amino acid residues of alternating hydrophobicity . This alternation results in a peptide amphiphile with distinct faces; the hydrophobic faces tend to interact and sequester the hydrophobic side chains, presenting the hydrophilic residues on the opposite surface for interaction with solvent .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While concerns about amyloidogenic potential of these beta structured peptides need further attention, in vitro and in vivo studies thus far have shown several classes of peptide‐based materials to be biocompatible . Beta‐sheet forming peptides often have the sequence (ZXZX) n , where Z and X represent amino acid residues of alternating hydrophobicity . This alternation results in a peptide amphiphile with distinct faces; the hydrophobic faces tend to interact and sequester the hydrophobic side chains, presenting the hydrophilic residues on the opposite surface for interaction with solvent .…”
Section: Resultsmentioning
confidence: 99%
“…Beta‐sheet forming peptides often have the sequence (ZXZX) n , where Z and X represent amino acid residues of alternating hydrophobicity . This alternation results in a peptide amphiphile with distinct faces; the hydrophobic faces tend to interact and sequester the hydrophobic side chains, presenting the hydrophilic residues on the opposite surface for interaction with solvent . The exposed hydrophilic face offers opportunity to initiate assembly with pH changes, increasing the likelihood of creating a peptide hydrogel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, bioactive synthetic surfaces formed by self‐assembled monolayers (SAMs) of functionalized nanoparticles have been frequently used in cell biology due to their small scale, unique physical properties, and multiple surface functionalization . Compared to the SAMs of simple bioactive molecules, SAMs of biofunctionalized nanoparticles have advantages due to the fact that these SAMs provide a large surface area that allows a multiplicity of contact points between the cells and the nanomaterials, resulting in a more efficient information transfer and multifunctionalities implemented in the same particle, in the nanoscale …”
Section: Introductionmentioning
confidence: 99%
“…Self-assembling peptide amphiphile nanofiber gels have been widely used in 2D and 3D cellular culture studies [13] and are promising candidates for regenerative medicine applications due to their biocompatibility, biodegradability, and incorporation of bioactive signals. [14,15] Peptide amphiphile systems have been extensively used in neural regeneration applications, and bioactive epitopes derived from ECM proteins, such as the laminin-derived IKVAV and YIGSR, fibronectin-derived RGD, and tenascin-C-derived VFDNFVLK sequences, have been shown to induce neural differentiation, attachment, and migration. [16][17][18][19] The imitation of ECM proteins is especially important in this context, as integrin receptors and similar mechanotransduction elements are essential for cellular adhesion, homing, and differentiation.…”
Section: Introductionmentioning
confidence: 99%